EFFICACY OF INTRAUTERINE INFUSION OF IMMUNOMODULATORS AND PGF2alpha IN THE TREATMENT OF ENDOMETRITIS IN BUFFALOES - RAJU, K G SOLMON; NAIDU, K VENUGOPAL; RAO, K SADASIVA (The Indian Journal of Animal Reproduction, 2023)
A total of 72 buffaloes suffering from endometritis were utilized for the study. The affected buffaloes12 each were treated with PBS, Lipopolysaccharides (LPS), Lysozyme (LZ), Oyster glycogen (OG),Vit. E and Selenium (SE); and PGF 2alpha  (PG) Vm. Higher percentage of buffaloes suffering from endometritiswas recovered with LPS (83.33), LZ (75.00), OG (66.67) and PGF 2alpha  (66.67) than the SE (50.00) andcontrol PBS ( 16.67). The conception rates were 53.33, 41.67, 33.33, 50.00, 25.00 and 16.67 In buffaloestreated with LPS, LZ, OG, SE, PG and untreated (PBS) groups, respectively. The bacterial colonycounts were 79.58± 8.10, 77.92 ± 5.15, 89.67 ± 5.05, 73.67 ± 7.33, 83.50 ± 6.19 and 70.86± 5.14before treatment in PBS, LPS, LZ, OG, SE and PG groups of buffaloes, respectively while the sameafter treatment were 126.83 ± 8.27; 6.67 ±1.39, 12.87 ± 3.35; 21.00 ± 5.93; 27.75 ± 4.10 and 24.75± 5.38, respectively. The progesterone (P4) profiles were 1.07±0.24; 0.81±0.10; 1.07:i:0.18; 1.03:t0.19; 0.98 ± 0.14 and 1.09 ± 0.14 ng /ml before treatment and 1.13±0.22; 0.32 :i: 0.03; 0.37 :i: 0.05;0.48 ± 0.07; 0.48 ± 0.08 and 0.40 ± 0.05 ng /ml after treatment in PBS control, LPS, LZ, OG, SE andPG groups, respectively.
Keywords: Endometritis; Buffaloes; lmmunomodulators; PGF2alpha